Pengaruh Good Governance dan Religiusitas terhadap Kecenderungan Fraud Dana Desa (Survei pada Pemerintahan Desa di Provinsi Daerah Istimewa Yogyakarta) - Fatmawati, Farida; Putra, Wahyu Manuhara (Ekonomis: Journal of Economics and Business, 2024)
This research aims to provide empirical evidence about the influence of the principles of transparency, accountability, responsibility, independence, fairness, & religiosity on the tendency of village fund fraud. The sample in this study was village government officials in the Special Region of Yogyakarta Province, using cluster-convenience sampling techniques. The number of respondents in this study was 154. This research is quantitative, using primary data obtained from distributing questionnaires to respondents. Hypothesis testing in this research used the SEM-PLS analysis. This research provides empirical results indicating that transparency has a negative & significant effect on the tendency of village fund fraud. Accountability, responsibility, fairness, & religiosity have a negative but not significant effect on the tendency of village fund fraud. Meanwhile, independence has a positive effect on the tendency of village fund fraud.